The Response of the Aerosol Distribution to Monsoon Intensity Over the Summer Monsoon Transition Zone - Bai, Bing; Zhang, Qiang; Shao, Wei; Wang, Ying; Tan, Dan (Frontiers in Earth Science, 2020)
The study region was the East Asian summer monsoon (EASM) transition zone. The datasets used in this study included the daily data of national stations, reanalysis datasets of the European Centre for Medium-Range Weather Forecasts (ECMWF), Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) and Moderate Resolution Imaging Spectroradiometer (MODIS) data. All datasets covered a total period of more than 1 year (from January 2008 to December 2016). We analyzed the influence of EASM on aerosol optical depth (AOD) in the transition zone and the response of different types of aerosols in the transition zone to the abundant and deficient monsoon years. It was found that the AOD was 0.15 in abundant years, while it was 0.09 in deficient years. The abundant year’s AOD was 40% larger than deficient years. In deficient years, with less precipitation, the influence of precipitation on the AOD was more significant. The dust was mainly distributed at 2–6 km in the western part of the transition zone, while the polluted aerosols were distributed at 0–4 km in the central and eastern region. The frequency of dust was significantly lower in abundant years, and dust particles accounted for about 19.6%. The frequency of polluted aerosols had an opposite trend, accounting for about 71.8%. Our findings bringed insight into the vertical distribution of aerosols in the atmospheric boundary layer and the interannual variation over the transition zone.